Captivating tourists to museums: Young versus senior museum visitors - Ferreira, E.S.; Loureiro, S. M. C. (Proceedings of the International conference on Tourism and Ageing., 2016)
Museums may act as a cognitive well-being process, where visitors may experience an enjoyable cognitive transformation. The main aim of the current study is to compare young and senior tourists in what concerns to capture and involve them to museums in Lisbon destination. The questionnaires were distributed over 2 months and a sample of 461 respondents was employed to treat and analyze data. Findings point out that young tourists are more engaged with using (interactive) panels, videos and audios as well as social interaction space than older visitors at museums. Older tourists tend to prefer to use guided tour, their own guide book and literature and even on-site online